2005
DOI: 10.1002/jso.20302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Siewert classification in gastro‐esophageal junction adenocarcinoma: What is the role of endoscopic ultrasonography?

Abstract: EUS seems to be essential in differentiating pT1 from advanced tumors. It shows an accuracy in defining the Siewert type of 72.5%, with some difficulties in distinguishing from type II and III tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…In total, 31 articles on EUS for regional lymph node metastases (Tio et al, 1990;Botet et al, 1991;Rice et al, 1991;Ziegler et al, 1991;Dittler and Siewert, 1993;Grimm et al, 1993;Greenberg et al, 1994;Yoshikane et al, 1994;Binmoeller et al, 1995;Hasegawa et al, 1996;Hunerbein et al, 1996;Natsugoe et al, 1996;Pham et al, 1998;Vickers, 1998;Bowrey et al, 1999;Catalano et al, 1999;Nishimaki et al, 1999;Salminen et al, 1999;Choi et al, 2000;Nesje et al, 2000;Richards et al, 2000;Shinkai et al, 2000;Vazquez-Sequeiros et al, 2001Rasanen et al, 2003;Wu et al, 2003;Heeren et al, 2004;Sihvo et al, 2004;DeWitt et al, 2005;Lowe et al, 2005;Pedrazzani et al, 2005) and five articles on EUS for celiac lymph node metastases were included (Binmoeller et al, 1995;Catalano et al, 1999;Eloubeidi et al, 2001;Vazquez-Sequeiros et al, 2001;Parmar et al, 2002) (Table 1). For CT, the literature search gave 1091 hits.…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…In total, 31 articles on EUS for regional lymph node metastases (Tio et al, 1990;Botet et al, 1991;Rice et al, 1991;Ziegler et al, 1991;Dittler and Siewert, 1993;Grimm et al, 1993;Greenberg et al, 1994;Yoshikane et al, 1994;Binmoeller et al, 1995;Hasegawa et al, 1996;Hunerbein et al, 1996;Natsugoe et al, 1996;Pham et al, 1998;Vickers, 1998;Bowrey et al, 1999;Catalano et al, 1999;Nishimaki et al, 1999;Salminen et al, 1999;Choi et al, 2000;Nesje et al, 2000;Richards et al, 2000;Shinkai et al, 2000;Vazquez-Sequeiros et al, 2001Rasanen et al, 2003;Wu et al, 2003;Heeren et al, 2004;Sihvo et al, 2004;DeWitt et al, 2005;Lowe et al, 2005;Pedrazzani et al, 2005) and five articles on EUS for celiac lymph node metastases were included (Binmoeller et al, 1995;Catalano et al, 1999;Eloubeidi et al, 2001;Vazquez-Sequeiros et al, 2001;Parmar et al, 2002) (Table 1). For CT, the literature search gave 1091 hits.…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…Nowadays the terminology used for the definition of adenocarcinomas at the GE junction is "cardiac carcinoma", which can be easily misunderstood. This definition of adenocarcinomas of the GE junction does not allow correct comparison of diagnosis (endoscopic, radiological and pathologic), epidemiology and surgical therapy in national and international aspects, because different tumor can develop in the same area, and all called cardia tumors [20] . Siewert and Stein recommended a classification to solve this problem [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Type Ⅱ is adenocarcinoma of the real cardia and type Ⅲ is subcardial gastric adenocarcinoma. The importance of this classification is it enables unified pre-operative assessment and it can also help to decide the type of the surgical intervention [20,[23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Total gastrectomy instead of esophagectomy may be an alternative surgical approach to Siewert type II-III tumors [2]. EUS combined with endoscopy may assist in determining the Siewert classification, although data on this are scarce [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pedrazzani et al [23] showed that the sensitivity and specificity for preoperative staging of Siewert type I cancers with a combination of endoscopy and EUS were 90 and 82 %, respectively, whereas these scores decreased to 75 and 69 %, respectively, when only endoscopy was performed. Distinguishing type II from type III lesions seemed even more difficult with sensitivities well below 75 %.…”
Section: Discussionmentioning
confidence: 99%